Sant'Ana dos Garimpeiros : cotidiano e religiosidade em Nortelândia (1959-1975) - Ormond, Katia Terezinha Pereira (2011)
This study addresses the migration of people to the North East of Mato Grosso, from the mid-twentieth century, and the cultural practices common to the small community emerged as a result of mineral exploration on the river Santana. In 1959, the party in honor of Our Lady Santana began shortly after the founding of the town of Nortelândia, a small town, which received people from different parts of Brazil especially the Northeast people, who was searching for the promises of getting rich quickly, generated by mining. So in this study we propose to analyze the relations established around the realization of these festivities, as well as record the way people live, pray and celebrate the religious festivity in Nortelândia. In preparing the study we used the methodology of oral history in which the interviews with ancient inhabitants of Nortelândia, especially with some women who has started the party, beyond the former party girl, were fundamental. The interviews were subsidized by handwritten documentation, printed and iconographic, such as newspapers, photos, invitations, reports available in the church of Sant’Ana, lists of novenaries and annual list of party-goers, who have given us the clues needed to understand the power relations established during these festivities. With these sources and making use of the relevant analysis to the historian, we understand more about the importance of this party to the region. Moreover, their life histories contribute to the recent history of Mato Grosso and Brasil and through these we can understand a little more about migration moviments, formation of new frontiers of colonization, and the importance of the religion in these people life.